Cultural Heritage Service Design and Experience Innovation: A Case Study of Taiwan - Ng, Wai-Kit; Chen, Chun-Liang; Jiang, Jhih-Ling; Shih, Ying-Shueh (Cultural Arts Research and Development, 2024)
This paper delves into the evolving landscape of community engagement, exploring innovative methods to enhance the involvement and awareness of young individuals. Employing a comprehensive content analysis through a multiple case study approach, this research investigates cultural heritage initiatives in Taiwan, emphasizing the pivotal role of technology and digital platforms in engaging young audiences. The study utilizes theoretical sampling and triangulation methods, incorporating semi-structured interviews, secondary sources, and participant observation. The findings underscore the significance of digital experiences as supplements to physical presence, offering a gateway to cultural heritage. The practical implications advocate for heritage sites to leverage digital platforms, collaborating with external partners to enrich visitor experiences. The paper furnishes valuable recommendations for enhancing customer engagement and communication with the younger demographic, contributing to the field of cultural heritage in Asia. This research marks a transition from physical to online service design, harnessing technology to inspire and engage, ultimately attracting diverse generations and retaining the interest of existing visitors.